Comparison of direct instruction and computer-assisted instruction on learning the skill off setting in volleyball. - Vernadakis, Νίκος; Antoniou, Παναγιώτης; Kellis, Ηρακλής; Kioumourtzoglou, Ευθύµης (Inquiries in Physical Education and Sport, 2003)
The purpose of this study was to determine the effect of computer – assisted instruction on learning the skill of setting in volleyball. The participants were 32 high school students of first and second grade, aged 12-14 years old, who were randomly assigned to one of two teaching method groups: a) traditional instruction (TI) and b) computer – assisted instruction (CAI). Each group received nine 40-min periods of instruction, on successive and separate days. TI group subjects experienced the skill of setting through a series of progressive skills accompanied with drill and repetition of practice presented by an instructor. The CAI group experienced the skill of setting through a series of progressive skills accompanied with drill and repetition of practice presented by a multimedia program. In the beginning and the end of this study the groups received a 10-item multiple-choice knowledge and a skill test. The result indicated that there were no significant differences between the TI and CAI groups concerning the knowledge and skill test. The results suggest that the multimedia technology as a teaching aid is as effective and profitable as the traditional teaching method on learning skills.